Transcatheter Arterial Coil Embolization of Ruptured Common Hepatic Artery Aneurysm in a Patient with Behçet’s Disease - Akihiro Hotta; Ryohei Kuwatsuru; Kouichi Asahi; Shingo Okada; Daisuke Tsuge; Akihiko Shiraishi; Yoshinari Takasaki (Case Reports in Radiology)
Hepatic artery aneurysm is a rare and potentially life-threatening entity. We report a case of ruptured common hepatic artery aneurysm in a patient with Behçet’s disease. The ruptured aneurysm was treated successfully with transcatheter arterial coil embolization. Transcatheter arterial embolization is the preferred treatment modality in patients at high risk of surgical intervention.